MIGRATION PROBLEMS IN TAJIKISTAN - KUDDUSOV, Jamshed (CENTRAL ASIA AND THE CAUCASUS, 2004)
Over the last 14 years, the ethnic picture of Tajikistan has changed a lot mainly under the pressure of the transition period. According to the 1989 population census, Tajiks (the title nation) comprised 62.3 percent of the total population; Uzbeks, 23.5 percent; Russians, 7.6 percent; Tartars,1.4 percent; the Kyrgyz, 1.3 percent; Ukrainians, 0.8 percent; Germans, 0.7 percent. All other ethnic groups, over 20 of them, accounted for less than 0.5 percent. According to the 2000 census, the share of Tajiks increased to 80 percent; the share of Uzbeks went down to 15.3 percent; Russians comprised 1.1 percent; Tartars, 0.3 percent; the Kyrgyz, 1.1 percent, Ukrainians, 0.1 percent; Germans, less than 0.1 percent. We should take into account that the country’s demographic potential is high: between the two censuses its population increased by 20.3 percent to reach 6,127,500. In these years the number of Afghans increased from 2.1 thous to 4.7 thous; Arabs, from 0.3 to 14.5 thous; Gypsies, from 1.8 to 4.2 thous. At the same time, new nationalities and ethnic groups appeared in statistical reports: Lakais, Kongrats, Mings, Dour-mens, Katagans, Barloses and others, with the total population of about 80,000. After 1991, when the republic became independent, it lived through one of the hardest periods in the history of the Tajiks: the transfer to market economy affected all spheres of life. The country was shaken by external catastrophes (disintegration of the Soviet Union and ruptured economic ties) accompanied by internal processes, especially the civil war that drove away many people between 1992 and 1997. Later, they all came back; the combination of all these processes spurred on migration. At present, the social-economic picture is not complete without external labor migration; it is the most important social phenomenon of the turn of the 21st century. Today, external labor migration is exerting decisive influence on the life-supporting system of nearly all Tajik families. There are obvious positive and negative effects; there are also other sides: rural-to-urban migration, migration between the regions, voluntary resettlement from the mountainous densely populated areas to the valleys and planned resettlement from exogenously dangerous to safer places. The scope of these changes cannot be compared, though, with that of external labor migration.